Pengelolaan dan Pelayanan Perpustakaan Dengan Sistem SLIMS 9 Berbasis Local Host - Tantri Rahayu; Fatimah Azzahri; Khoirunnisa, Khoirunnisa; Suhariyanti, Suhariyanti (PT. ALHAFI BERKAH INDONESIA, 2024)
The development of information technology in the current technological era is growing very rapidly. The development of information technology has had a major influence on the development of libraries, especially in terms of managing information. Indeed, it is not something bad or even prohibited if you continue to manage the library using manual methods, there are several things that need to be considered, why libraries in the current context need an automation system. All libraries are required to be able to keep up with advances in information technology in the current are of digitalization. Libraries currently also have to implement an automation system using a set of computer tools assisted by supporting software such as SLIMS 9 (Senayan Library Management System). SLIMS 9 is very helpful for librarians’ work in processing library materials. Inventory, classification, cataloging and labeling are no longer done manually but are automated with a SLIMS-based library automation system. The problems that we often encounter today are not fully implementing SLIMS 9 propely and inadequate Human Resources (HR), so we have to recollect data on collections of library materials available using SLIMS 9. Using SLIMS 9 can help libraries in increase efficiency and availability of information. The use of SLIMS 9 varies depending on the scale and needs of each library, from school libraries to university libraries or public libraries. Good implementation usually involves training library staff to make optimal use of these system features.